Ensuring supply and creating demand for a biofortified crop with a visible trait: Lessons learned from the introduction of orange-fleshed sweet potato in drought-prone areas of Mozambique - Low, Jan Wayland; Arimond, Mary; Osman, Nadia; Cunguara, Benedito; Zano, Filipe; Tschirley, David (SAGE Publications, 2007)
Background. Orange-fleshed sweet potato (OFSP) is a promising biofortified crop for sub-Saharan Africa because it has high levels of provitamin A carotenoids, the formed vitamin A is bioavailable, and white-fleshed sweet potato is already widely grown. Objectives. To examine whether farmers will adopt varieties with a distinct visible trait, young children will eat OFSP in sufficient quantities to improve vitamin A intake, OFSP can serve as an entry point for promoting a more diversified diet, and lessons can be drawn to assure sustained adoption. Methods. The 2-year quasi-experimental intervention study followed households and children (n = 741; mean age, 13 months at baseline) through two agricultural cycles in drought prone-areas of Mozambique. Results. OFSP is acceptable to farmers when introduced by using an integrated approach. In the second year, intervention children (n = 498) were more likely than control children (n = 243) to have consumed OFSP (54% vs. 4%), dark-green leaves (60% vs. 46%), or ripe papaya (65% vs. 42%) on 3 or more days in the previous week (p < .001 for all comparisons). Their vitamin A intakes were nearly eight times higher than those of control children (median, 426 vs. 56 µg RAE [retinol activity equivalents], p < .001). Diet diversification was limited by difficult agroecological conditions and low purchasing power. However, dietary diversity was higher among intervention than control children (32% vs. 9% consuming food from more than four groups; p < .001). Conclusions. An integrated OFSP-based approach had a positive impact on the vitamin A intake of young children. A market development component and improved vine multiplication systems are recommended to assure sustained adoption